Hypodematium zhangii (hypodematiaceae) – a new species recorded from china - Li, Xiaojuan; Zhang, Chao; Liu, Ruigui; Li, Jianxiu; Shu, Jing (Bangladesh Journal of Botany, 2024)
Hypodematium zhangii J. X. Li & X. J. Li, a new species of Hypodematium is recorded from Guangxi Zhuang Autonomous Region, China. It is similar to H. crenatum (Forssk.) Kuhn & Decken, but differs greatly from it by its stipe glabrous, rachis and fronds sparsely covered with hispidity adaxially, indusia and fronds densely coated with hispidity abaxially and spores perispore with tuberculate and massive protrusions, surface with scaly ornamentation. The description and photographs of H. zhangii as well as their notes are provided. Bangladesh J. Bot. 53(3): 795-802, 2024 (September) Special